Analysis of Information Technology Governance In Bina Darma Foundation of Salatiga Using COBIT 5 Framework - Puspitasari, Dwi; Chernovita, Hanna Prillysca (Asosiasi Doktor Sistem Informasi Indonesia, 2021)
Bina Darma foundation is a non-profit organization established by SWCU and GMKI. The main activities of the Bina Darma foundation are a leadership training program, journal publishing, and guesthouse rental. Problems that occur in the foundation include the management of human resources related to IT is not appropriate. To solve the problem, there needs to be control and evaluation to see how the condition of IT governance in Bina Darma Foundation uses the framework COBIT 5 domain DSS (Delivery, Service, and Support). The result of this research is capability level is currently at level 1 (Performed process), while the capability level is expected to be at level 2 (Managed process). Therefore, recommendations are given so that the IT governance in Bina Darma Foundation can work optimally to support the achievement of the organization's business objectives efficiently.